Penerapan Total Quality Management dan ISO 9000 dalam Pendidikan Teknik - Ahmad Sonhadji K. Hasan (Universitas Negeri Malang, 2016)
An organization is able to improve and maintain its quality by building a quality improvement system, and determining the quality standards. For satisfying industry requirements in providing human resources, technical education must continuously improve its quality. The need can be effectively achieved by appliying TQM and ISO 9000. TQM is a quality improvement system for meeting customer requirements, and ISO 9000 is an international certification for standards of design, production, instalation, and servicing